Упростите выражение 1)3(-2х-4)+2(3х+8)+2х= 2)-5а-5(-а+8)-14= 3)3а-(10-3а)= 4)3(-8х+4)+2(12х-8)+2х= 5)у-3у= 6)-16t+15t= 7)-15-3t+20= 8)7-2y+3y+2= 9)3/28y+3/4y= 10)-4/5b+6/15b=

Упростите выражение 1)3(-2х-4)+2(3х+8)+2х= 2)-5а-5(-а+8)-14= 3)3а-(10-3а)= 4)3(-8х+4)+2(12х-8)+2х= 5)у-3у= 6)-16t+15t= 7)-15-3t+20= 8)7-2y+3y+2= 9)3/28y+3/4y= 10)-4/5b+6/15b=
Гость
Ответ(ы) на вопрос:
Гость
1) -6x-12+6x+16+2x= 4+2x 2) -5a+5a-40-14= -54 3) 3a-10+3a= 6a-10 4) -24x+12+24x-16+2x= -4+2x 5) y-3y= -2y 6) -16t+15t= -t 7) -15-3t+20= -3t+5 8) 7-2y+3y+2= 9+y 9) 3/28y+3/4y= 3/28y+3/4y(×7) = 3/28y+21/28y= 24/28 = 6/7 10) -4/5b+6/15b = -4/5b(×3)+6/15b = -12/15b+6/15b= -6/15b = -2/5b
Не нашли ответ?
Ответить на вопрос
Похожие вопросы